Mesenchymal Stem Cell Engagement Modulates Neuroma Microenviroment in Rats and Humans and Prevents Postamputation Pain - Casadei, Inelia Mailín Iara (2024)
Postamputation pain is currently managed unsatisfactorily with neuron-targeted pharmacological and interventional therapies. Non-neuronal pain mechanisms have emerged as crucial factors in the development and persistence of postamputation pain. Consequently, these mechanisms offer exciting prospects as innovative therapeutic targets. We examined the hypothesis that engaging mesenchymal stem cells (MSCs) would foster local neuroimmune interactions, leading to a potential reduction in postamputation pain. We utilized an ex vivo neuroma model from a phantom limb pain patient to uncover that the oligodeoxynucleotide IMT504 engaged human primary MSCs to promote an anti-inflammatory microenvironment. Reverse translation experiments recapitulated these effects. Thus, in an in vivo rat model, IMT504 exhibited strong efficacy in preventing autotomy (self-mutilation) behaviors. This effect was linked to a substantial accumulation of MSCs in the neuroma and associated dorsal root ganglia and the establishment of an anti-inflammatory phenotype in these compartments. Centrally, this intervention reduced glial reactivity in the dorsal horn spinal cord, demonstrating diminished nociceptive activity. Accordingly, the exogenous systemic administration of MSCs phenocopied the behavioral effects of IMT504. Our findings underscore the mechanistic relevance of MSCs and the translational therapeutic potential of IMT504 to engage non-neuronal cells for the prevention of postamputation pain.